A good teacher in the understanding of students of pedagogy A phenomenographic reconstruction - Sławińska, Małgorzata (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
The following text is a phenomenographic reconstruction of students’ conceptions of a good teacher. The research has been based on the comments of students of pedagogy on the best teachers they were taught by on different levels of education. The interpretation of the materials gathered formed the following categories of „good teacher” by the students of pedagogy: „an educator with a twinkle in their eye”, „a tutor who really cares”, „heart of gold”, „the Socrates of today”. The points of reference for the students’ conceptions are selected examples of a good teacher in various works of philosophers, pedagogists and psychologists as well as modern conceptions of teacher professionalism.